Analysis of the Impact of Refactorings on the Performance of Embedded Systems - Reis Filho, Heitor Boeira dos; Corrêa, Ulisses B.; Duarte, Lucio Mauro; Beck, Antônio C. S. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
In recent years, the large growth of embedded platforms available in the market brought a great challenge to software developers, since this kind of system offers limited hardware resources, which are lower than desktop computers. Therefore, these must be optimally used by programmers in order to meet expectations of end-users, such as performance, usability and battery life. In this context, this work aims to study the impact of code recapturing on the embedded devices' performance. This study is done by source code recapturing, aiming to improve readability and performance without altering the original functionality of the requirement. Three basic refactorings were evaluated and the Mult2Sim processor simulator was used.